(3GddeY aj CUhd Gdabgs - (3EHQGgje Hf Ydj Hf jhSa GdTjQGRj GdajQhRGHGOj , CHh ESMGb , LeGd GdOjf,J (B476 (3g` s ((3GdCScfOQjI s)
(3ChdgG (B:s
(3GdMeO ddg ceG gh Cgdg SCdfi HYV ENhGfi Cf CUfa dge eNJUQkG ai GdePgH ai CUhd Gdabg aCLHJg Edi Pdc s
(3BNQgG (B:s
(3BNQ GdehLhO efg ai HGH Gdbhd ai JQLjM CMO GdNHQjf Ydi GdBNQ (B: ( (3hefge ef bGd fQLM CMO GdQhGjJjf Yef ENJdaJ GdQhGjI Yfg Ydi GdQhGjI GdCNQi (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B68s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1562s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3CUhd Gdabgs